Wetland Delineation: An Overview of Regulations and Methods - Daniel L. Irick; Yuncong Li; Alan L. Wright (EDIS)
SL289, a 4-page illustrated fact sheet by Daniel L. Irick, Yuncong Li, and Alan L. Wright, describe the regulatory nature of wetland delineation and classification for landowners, wetland and soil scientists, and the general public. Includes references. Published by the UF Department of Soil and Water Science, May 2009.